Bahasa dan Otak: Bagaimana Pikiran Membentuk Komunikasi: Bahasa dan Otak: Bagaimana Pikiran Membentuk Komunikasi - fibri ulya zahra; Silvina noviyanti; Azizah; Yosi Yuliana Lumbantobing (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Language is a unique human ability that heavily depends on the brain's function as the center for processing and producing communication. This study aims to examine the relationship between language and the brain in shaping the human communication process. The method used in this research is a literature review by collecting and analyzing various scientific sources related to neurolinguistics and brain function in language use. The results show that the brain is divided into two main hemispheres; the left hemisphere plays a role in language, analysis, and logic, while the right hemisphere contributes to creativity and emotional expression. The Broca and Wernicke areas in the left brain hemisphere are the main centers for language production and comprehension, connected by the arcuate fasciculus nerve pathway. Language and thought interact in a complex manner, where the brain not only stores words but also regulates language use according to social context and individual experience. This study also emphasizes the importance of neurolinguistics in overcoming language disorders as well as in the development of education and modern communication technology. In conclusion, the relationship between language and the brain is a fundamental basis in human communication and cultural development, which helps build better learning methods, language therapy, and technology.